Banking and Industrialization - Stephan Heblich; Alex Trew (Center for Economic Studies and ifo Institute (CESifo), 2015)
We exploit employment data from 10,528 parishes across nineteenth century England and Wales and find that a one standard deviation increase in finance employment increases the annualized growth rate of secondary labour by 0.8 percentage points. An endogenous growth model with finance and structural transformation motivates the empirical approach. Since initial banking access in 1817 may have been endogenously determined, we use instrumental variables to predict the location of country banks founded before the industrial take-off could possibly be expected. Distance and subsectoral analysis suggest that the effect of finance is highly localized and particularly strong for intermediate secondary sectors.
Keywords: O11; O16; O40; N23; R11; 330; banking; industrial revolution; structural transformation; regional economic growth; urbanization